the PENGARUH CERITA DIGITAL TERHADAP KETERAMPILAN MENULIS KARANGAN NARASI SISWA SEKOLAH DASAR: PENGARUH CERITA DIGITAL TERHADAP KETERAMPILAN MENULIS KARANGAN NARASI SISWA SEKOLAH DASAR - Marisatul Mahfudhoh; Ermawati Zulikhatin Nuroh (Jurnal Semantik, 2024)
The background of this study is the lack of student's ability to write and the lack of teachers using media in narrative essay material. The purpose of this study was to analyze the effect of digital storytelling on the writing skills of fourth-grade students of SDN Sentul. The research method used in this study is a quantitative method with a one-group pretest-posttest design. Research data collection techniques in the form of tests and documentation, the research subjects used were 20 fourth-grade students of SDN Sentul. The research assessment process uses a rubric of narrative essay writing skills that contains the content of ideas, organization of essay content, grammatical structure, diction, spelling, and punctuation. The results of the study obtained a significant value (2-tailed) worth 0.000 from the results of the one sample T-test, namely the Sig value of 0.000 <0.05 then H0 is rejected and for Ha is accepted. Thus, it can be concluded that digital story media affects the narrative essay writing skills of elementary school students. Thus, digital stories can be used as an alternative method in writing classes for teachers who are looking for media in the digital age.